Nurses’ Job Burnout: A Hybrid Concept Analysis - Nabizadeh-Gharghozar, Zohreh (J Caring Sci, 2020)
Introduction: Job burnout can significantly affect nurses’ physical and mental health and the quality of the care services they provide. Yet, there is no clear definition for job burnout in nursing. This study aimed to analyze the concept of nurses’ occupational burnout. Methods: This concept analysis was conducted, using the three-phase hybrid model. In the theoretical phase, online databases, namely Iranmedex, Scientific Information Database (SID), Science Direct, MagIran, ProQuest, Web of Sciences, Scopus, and PubMed were searched to retrieve studies published from 2007 to 2018. In the fieldwork phase, twelve semi-structured interviews were conducted with nurses and head-nurses selected from teaching hospitals in Isfahan, Iran. The interviews were transcribed and analyzed through thematic analysis. In the final analytic phase, the findings of the first and the second phases were combined. Results: Based on the findings of the theoretical and the fieldwork phases, job burnout can be defined as, “a state of physical, mental, emotional, and social exhaustion resulting from the negative effects of unmanaged occupational stress and inadequate managerial and social support, which reduces interest in and motivation for work, affects care quality, and results in negative attitudes and behavior towards self, clients, and the work”. Conclusion: This study provides an in-depth understanding of the concept of job burnout in the nursing context of Iran. Managers need to develop strategies for job burnout prevention and management based on its contributing factors.